(untitled) (Academia Journal of Medicine, 2025)
An online survey was conducted among practicing dentists using an online questionnaire to assess the awareness, acceptance, and clinical usage of SDF. 500 dentists participated in the online survey. The data obtained were analysed statistically. The survey maps awareness, acceptance, and clinical use of SDF among Indian dentists, showing limited clinical uptake despite favorable attitudes, with knowledge gaps as the principal barrier.